Calcium phosphate formation and deposition in ischemic neurons. - Shu Q Liu; John B Troy; Jeremy Goldman; Roger J Guillory (PLoS ONE)
Ischemic stroke causes acute brain calcium phosphate (CaP) deposition, a process involving primarily the injured neurons. Whereas the adverse impact of CaP deposition on the brain structure and function has been recognized, the underlying mechanisms remain poorly understood. This investigation demonstrated that the neuron-expressed, plasma membrane-associated Ca2+-binding proteins annexin (Anx) A2, AnxA5, AnxA6, and AnxA7 contributed to neuronal CaP deposition in the mouse model of ischemic stroke. These Anxs were released from the degraded plasma membrane of the ischemic neurons and were able to form Anx/CaP complexes, a nanostructure capable of binding to the β actin filaments via Anx-actin interaction to cause neuronal CaP deposition prior to brain infarction. Anx administration to the healthy mouse brain caused brain CaP deposition and infarction. Monomeric β actin was able to block competitively Anx binding to β actin filaments and prevent ischemic stroke- and Anx administration-induced brain CaP deposition and infarction. Administration of siRNAs specific to the four Anx mRNAs alleviated brain CaP deposition and infarction. These observations support the role of Anxs in CaP formation and deposition in ischemic neurons.